2017
DOI: 10.4236/ojepi.2017.74027
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Factors Associated with Home Delivery in a Situation of Free Care in Senegal

Abstract: Introduction: Home delivery is still a health problem in Kolda (Senegal). The aim of this work is to study the factors associated with the place of delivery in a situation of free care delivery. Method: A descriptive and analytical cross-sectional study was carried out. Sampling was in two-stage clusters. The study focused on women who gave birth in the last 12months. The data were collected during an individual interview at home. The collection focused on knowledge, attitudes and practices about delivery. Log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Studies from Kathmandu, Nepal, and Malawi showed a strong connection between no/fewer than four ANC visits and home delivery [ 28 , 98 ]. Additionally, this finding is consistent with studies conducted in Eretria [ 99 ], Bhutan [ 100 ], and Senegal [ 69 ]. The possible reason might be women who had no/few ANC follow-up might be less aware of birth preparedness and complication readiness plan, danger signs of pregnancy, when to visit health facilities, and the danger of giving childbirth at home which increases the probability of home childbirth.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Studies from Kathmandu, Nepal, and Malawi showed a strong connection between no/fewer than four ANC visits and home delivery [ 28 , 98 ]. Additionally, this finding is consistent with studies conducted in Eretria [ 99 ], Bhutan [ 100 ], and Senegal [ 69 ]. The possible reason might be women who had no/few ANC follow-up might be less aware of birth preparedness and complication readiness plan, danger signs of pregnancy, when to visit health facilities, and the danger of giving childbirth at home which increases the probability of home childbirth.…”
Section: Discussionsupporting
confidence: 92%
“…The result is in line with a study extracted from the 2016 Ethiopia Demographic and Health Survey accounting for 67.2% of mothers giving birth at home [ 90 ]. However, the result is higher than the study in Nepal [ 91 ] 41.9%, Senegal [ 69 ] 43.5%, and Guinea-Bissau [ 92 ] 61.2%, quite possibly due to difference in the availability of transportation, distance from the health facility, health literacy, wealth index, access to media like listening to radio/watching TV, mothers’ level of education, and knowledge of birth preparedness and complication readiness plan. As per the authors’ knowledge, this is the first systematic review and meta-analysis in Ethiopia to estimate the pooled prevalence and determinants of home childbirth.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation